Handbook of Research on Healthcare Administration and Management. (IGI Global, 2016)
"This book is a pivotal reference source for research material on emerging strategies and methods for delivering optimal healthcare opportunities and solutions, highlighting issues relating to decision making, process optimization, and technological applications"--Provided by publisher.
Keywords: zdravotnický management; zdravotní péče; lékařská informatika; zpracování dat; health service management; health care; medical informatics; data protection; příručky; elektronické knihy; handbooks and manuals; electronic books